The impact of non-financial resources on the perceived dependency of non-profit organisations in relation to the state: the Portuguese case - Macedo, Isabel Maria (2001)
In the context of an extensive sharing of responsibility between governmental and non-profit organisations to accomplish social policy actions, the relationship between state and the nonprofit organisations and the degree of dependence of these organisations in relation to the state has been acknowledged as a critical issue within social and public policy. However, the hallmark of much research related with non-profit/statutory relations has derived mainly from the widely recognition of non-profit s increased income from statutory sources (Salamon and Anheier, 1996). As a result, non-profit s dependency on the state has been captured essentially by assessing financial dependency. Assuming that nonprofit organisations are also dependent on the state for non-financial resources (Saidel, 1991; 6,1994), this paper attempts to analyse the extent to which the non-profit sector is dependent on the state for resources, as well as evaluating the weight that non-financial resources might have in the perceived resource dependency assumed by non-profit organisation s managers in relation to the state.